Information Technology Risk Management in Educational Institutions Using ISO 31000 Framework - Putri, Niken Lusia; Wijaya, Agustinus Fritz (Journal of Information Systems and Informatics, 2023)
As information technology becomes increasingly integrated into daily business processes within educational institutions in Indonesia, the need to address potential risks associated with this integration has become crucial. This research focuses on analyzing information technology risk management in Indonesian educational institutions using the ISO 31000 framework. The study aims to minimize the occurrence and impact of various information technology risks that can disrupt organizational processes. Through a comprehensive examination encompassing risk assessment, analysis, evaluation, and treatment, this research provides valuable insights into identifying potential risks within educational institutions. Furthermore, the findings serve as a reference for formulating risk management policies, enabling institutions to proactively mitigate the possibility of information technology risks and their future impact. By adopting the ISO 31000 framework, educational institutions can enhance their efficiency, effectiveness, and accessibility while safeguarding against potential disruptions.